2017
DOI: 10.1007/s00705-017-3606-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of three porcine bocaparvoviruses and identification of a natural recombinant breakpoint in NS1

Abstract: In this study, we obtained the whole genomes of three porcine bocaparvovirus (PBoV) strains (GD6, GD10, and GD23) by polymerase chain reaction. Sequence analysis showed that all three field strains belonged to PBoV group 3 (G3). The phylogenetic trees based on NS1, NP1, and VP1 differed to the extent that these PBoVs were potentially more closely related to bocaparvoviruses known to infect other animals than to other PBoVs. GD6, GD10, and GD23 all included the conserved sequences YLGPF and HDXXY, with known ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…According to the qPCR detection results of 281 clinical samples, 148 samples (148/281, 52.67%) were positive for PBoV1/2, 117 samples (117/281, 41.63%) were positive for PBoV3/4/5, 55 samples (55/281, 19.57%) were positive for both PBoV1/2 and PBoV3/4/5, and PBoVs were detected on 32 pig farms in 17 cities except Pingdingshan (Table 1), with 86.89% (32/37) of pig farms harboring PBoVs, indicating that PBoV was currently circulating in swine herds in central China. Overall, the prevalence of PBoV was 74.73% in central China (210/281), and it was much higher than that of previous reports (Zhang et al 2015;Zhou et al 2018b) which showed that PBoV mainly distributed in the east and south coastal areas of China. The results suggested that PBoV has broadly distributed among swine farms in diarrheal piglets in China.…”
Section: Resultscontrasting
confidence: 63%
“…According to the qPCR detection results of 281 clinical samples, 148 samples (148/281, 52.67%) were positive for PBoV1/2, 117 samples (117/281, 41.63%) were positive for PBoV3/4/5, 55 samples (55/281, 19.57%) were positive for both PBoV1/2 and PBoV3/4/5, and PBoVs were detected on 32 pig farms in 17 cities except Pingdingshan (Table 1), with 86.89% (32/37) of pig farms harboring PBoVs, indicating that PBoV was currently circulating in swine herds in central China. Overall, the prevalence of PBoV was 74.73% in central China (210/281), and it was much higher than that of previous reports (Zhang et al 2015;Zhou et al 2018b) which showed that PBoV mainly distributed in the east and south coastal areas of China. The results suggested that PBoV has broadly distributed among swine farms in diarrheal piglets in China.…”
Section: Resultscontrasting
confidence: 63%
“…The conserved motif YXGXF carried by porcine bocavirus is different from the YXGXG motif of other parvoviruses (Cheng et al 2010;Zhou et al 2017). However, in addition to the HDXXY motif and YXGXF motif other motifs have been reported in PBoV, including the HDQAY motif in strain GD6, the HDLAY motif in strain GD10, and the YLGPF motif in strains GD6, GD10, and GD23 (Zhou et al 2017). The function of the protein encoded by ORF-3 is not clear, but in CMV, it has been associated with viral replication (Lau et al 2011).…”
Section: Genomic Characteristicsmentioning
confidence: 82%
“…PBoV, which is a nonenveloped virus, exhibits icosahedral symmetry (Cheng et al 2010;Zhou et al 2017), has a diameter of 26-30 nm (Yang et al 2012) and consists of linear, single-stranded DNA of 4-6 kb (Cheng et al 2010;Zhou et al 2017) of either positive or, most often, negative polarity, with most strains being negative-sense (Anne Christin Böhmer et al 2009). As shown in Fig.…”
Section: Genomic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations